Haptic demonstration via teleoperation - Lim, Hao Jie (Nanyang Technological University, 2020)
A human can intuitively manipulate the object through their hand. The ease of programming in robots for the same task is challenging. A possible solution can be learning by demonstration. Haptic feedback can be used to facilitate the demonstration process. The user perceives the haptic feedback and can predict and prevent unstable manipulation. Evaluating different control strategies and implementing haptic feedback during bimanual teleoperation. A 2 degree of freedom (DOF) bimanual master-slave system will be used to evaluate different control strategies. HEBI series elastic actuator will be used as the actuator. The result shows that position-force control has the ideal performance when a slave robot is moving without interaction. Variable impedance control outperforms other strategies at the transition phase of the slave robot is moving without interaction and with interaction.